Business for sustainability, volume I Strategic avenues and managerial approaches - Vrontis, Demetris; Thrassou, Alkis; Efthymiou, Leonidas; Weber, Yaakov 19XX-; Shams, S. M. Riad 1979-; Tsoukatos, Evangelos (palgrave macmillan, 2023)
Part of a two-volume work, this book explores how businesses shape, and are shaped by, sustainability forces and phenomena. These evolutionary transformations have driven scholars, practitioners and decision makers to pay increased attention to sustainability as an integral part of business development. Both volumes offer a cross-section of multi-disciplinary perspectives within business studies. Volume 1 focuses on strategic and managerial approaches to sustainability in business, including accounts on the historic origins of sustainability and its contemporary corporate sustainable models. Volume 2 explores, more contextually, how business and social sustainability constitute indivisible and inextricable components of the same nexus. Taken together, they offer an original perspective on how businesses can help achieve the SDG goals and targets. Demetris Vrontis is Professor and Vice Rector for Faculty and Research at the University of Nicosia in Cyprus, the Editor-in-Chief of the EuroMed Journal of Business, and President of the EuroMed Academy of Business. Alkis Thrassou is Professor and Director of Gnosis Mediterranean Institute for Management Science at the University of Nicosia, Cyprus. Leonidas Efthymiou is Assistant Professor in the School of Business, at the University of Nicosia, Cyprus. Yaakov Weber is Professor and Director of the Research Unit, School of Business Administration, College of Management, Israel, and President of the EuroMed Academy of Business. S. M. Riad Shams is Senior Lecturer at the Newcastle Business School, Northumbria University, UK, and the founding editor of the International Journal of Big Data Management. Evangelos Tsoukatos teaches Management at the University of Applied Sciences, Greece, and is Associate Editor of the EuroMed Journal of Business (EMJB).
Chapter 1: An Overview of Business for Sustainability: Strategic Avenues and Managerial Approaches -- Chapter 2: Exploring Consumer Boycott Intention towards Corporate Sustainable Business Practices -- Chapter 3: Sustainability of Youth Development in Drylands: A Systematic Approach -- Chapter 4: Investigating the Supply Chain Performance of Agribusiness firms from the IT Capability and Government Support Perspectives -- Chapter 5: Sustainable Partnership Responses to Prevent Homelessness from Hospital Discharges and Prison Releases: The case of Leeds City Council in the UK -- Chapter 6: Green Economy and Credit Quality in the European Banking Industry: What are the Opportunities for Sustainability? -- Chapter 7: Corporate Environmental Performance and Bond Ratings: European Evidence -- Chapter 8: Are Football Societies aware of the relevance of Diversity in Good Governance? The case of "Pink Quota" -- Chapter 9: How do Companies conceive Sustainable Infrastructure? Evidence from Construction Companies’ Reports Content Analysis -- Chapter 10: Weak Sustainable Development Trajectories and Evolving Organisational Physiologies: Empirical Evidence from Greece -- Chapter 11: Sustainability for Healthcare Organisations and Systems: Cultivating Strategy and Governance Processes for a Better Future -- Chapter 12: Cause-Related Marketing and Philanthropy at Times of Crisis and Increasing Digitisation
Keywords: Management; Industrial management -- Environmental aspects; Aufsatzsammlung